Causal relationship between health insurance and overall health status of children: Insights from Pakistan - Aziz, Noshaba; Liu, Tinghua; Yang, Shaoxiong; Zukiewicz-Sobczak, Wioletta (Frontiers in Public Health, 2022)
Evaluating the impact of health insurance always remains a methodologically challenging endeavor due to the absence of sample randomization. This paper evaluates the impact of health insurance on the health status of children in Pakistan using the data of the Multiple Indicator Cluster Survey (MICS) for Punjab, Pakistan, from 2017 to 2018. The study adopted the propensity score matching (PSM) method to address the sample selection bias. The sample is matched on potential covariates such as mother characteristics (education level), household head characteristics (gender, age, and education), and other household conditions (such as home dwelling, internet access, wealth index, migration member, number of children residing in the home, as child illness, etc.). The findings revealed that children with insurance have considerably better health than non-insured, at a 1% significance level. The results confirm that health insurance is not a luxury but a need that improves children's overall health. In this regard, governments should enhance and expand programs related to health insurance, especially for children. Health insurance programs will not only help poor people but also improve the overall infrastructure of health services in the country.